Effect of counseling on knowledge and attitudes for family planning among postpartum women delivering at a tertiary care hospital in Central Gujarat: An interventional study - Sangita Patel; Swapnil Malkhede; Priyash Sheth; Maitri Shah; Latika Tarun Chugh (Indian Journal of Community and Family Medicine, 2025)
Introduction: Unmet needs reduced from 13% to 9% among married women according to the NFHS 5 data. Misconceptions can result in unsafe abortions, unwanted pregnancies, and higher maternal and infant mortality risks. Hence, the present study was conducted to evaluate the difference in knowledge and attitude of family planning methods before and after counseling. Material and Methods: A nonrandomized trial was conducted among 206 postpartum women who delivered at the Department of Obstetrics and Gynecology in SSG hospital, Vadodara, for 2 years. One hundred and three participants in each group, i.e. control group and intervention group were interviewed. Intervention group counseling was done followed by a 10-min Hindi video, and informational leaflets about family planning methods were provided. One-week washout period was kept; afterward, control group counseling was given by standard counselor. Follow-up assessments after six months were conducted through home visits or telephone interviews. Data were collected, entered in Excel Spreadsheets, and analyzed using MedCalc. Results: The intervention group showed a significant improvement in knowledge postintervention, with a mean knowledge score of 17.53 ± 4.59 compared to the baseline mean of 11.84 ± SD 5.45 (p < 0.0001). However, there was no significant difference in baseline knowledge between the intervention and control groups. Postintervention, the intervention group had significantly higher knowledge scores (17.53 ± 4.59) compared to the control group (11.41 ± 5.27) (p < 0.0001). Conclusion: In this study, it was observed that improvement in knowledge and attitude was noticed in women in both intervention and control groups, but the improvement was significantly higher in the intervention group compared to the control group.